Design of Teaching Materials of Physics Based on Cognitive Conflict Integrated by Virtual Laboratory on Quantum Phenomenon - Noer, Fadhlina; Mufit, Fatni (PILLAR OF PHYSICS EDUCATION, 2023)
Nowadays, 21st century skills are needed to enter the era of globalization which is marked by the ease of accessing technology, causing information to spread quickly and widely. To be able to analyze information on technology Education applies the 2013 curriculum which requires the students to be able to comprehend concepts. However, in reality students' ability to understand concepts is still relatively low than average. There are the solutions of the issue such as to design teaching materials of physics based on the cognitive conflict models to improve students' conceptual comprehension. The aim of this research such as to design as well as to determine the validity of teaching materials for physics based on cognitive conflict. This teaching material uses the syntax of the cognitive conflict-based learning model which consists of 4 syntaxes, namely: first, activation of preconceptions and misconceptions, second is presentation of cognitive conflicts, the third is discovery of concepts and similarities, and lastly reflection. In the third syntax, a virtual laboratory is integrated by PhET such as blackbody spectrum and photoelectric effect. The validation’s results of the teaching materials based on cognitive conflict on quantum phenomena are 0.88. Obtaining these values, the design of teaching materials of physics based on cognitive conflict is declared valid in the aspects of content feasibility, presentation feasibility, language feasibility, and graphic feasibility. So, the research it can be continued at the practicality and effectiveness research stage in order to produce teaching material which suitable for learning process.